BCORL1 S878G, GNB1 G116S, SH2B3 A536T, and KMT2D S3708R tetramutation co-contribute to a pediatric acute myeloid leukemia: Case report and literature review - Wang, Liang; Chen, Sen; Shen, Yongming; Si, Ping (Frontiers in Pediatrics, 2022)
Acute myeloid leukemia (AML) is a clinically, morphologically, and genetically heterogeneous group of malignancies characterized by a wide range of genomic alterations responsible for defective regulation of the differentiation and self-renewal programs of hematopoietic stem cells. Here, we report a 4-month-old boy who had acute onset with leukocytosis and abdominal mass. The morphological analysis of bone marrow (BM) smear revealed extremely marrow hyperplasia, large quantities of immature cells, and primary and immature monocytic hyperplasia accounting for 57.5% of nucleated cells. The chromosome karyotype of the case was complex, representing 48, XY, +13, +19[12]/48, idem, del (p12)[8]. After RNAs sequencing, a mutation (c.346G > A, p.G116S) of the GNB1 gene was detected and localized to the mutational hotspot in Exon 7. Meanwhile, the other three mutations were identified by next-generation sequencing (NGS) and whole-exome sequencing (WES) of DNA from the BM aspirate and oral swab, including BCORL1 mutation [c.2632A > G, p.S878G, mutation allele frequency (VAF): 99.95%], SH2B3 mutation (c.1606G > A, p.A536T, VAF: 51.17%), and KMT2D mutation (c.11124C > G, p.S3708R, VAF: 48.95%). BCORL1 mutations have been associated with the pathogenesis of AML, whereas other mutations have rarely been previously reported in pediatric AML. The patient did not undergo the combination chemotherapy and eventually died of respiratory failure. In conclusion, the concurrence of BCORL1, GNB1, SH2B3, and KMT2D mutations may be a mutationally detrimental combination and contribute to disease progression.